The Effect Of Menu Variation, Taste, And Service Quality On Purchase Decisions At The Qof Coffee Cafe Business In Lubuklinggau City - Penti Nopiyanti; Ermy Wijaya; Siti Hanila (Journal of Business Management, 2026)
This study aims to examine the impact of menu variety, taste, and survice quality on consumer purchasing decisions at Cafe Qof Coffee in Lubuklinggau City. A quantitative approach was employed through a survey method using questionnaires distributed to 100 consumer respondents of Cafe Qof Coffee. Respondents were selected using accidental sampling technique. Subsequenty, the data were analyzed using multiple liner regression with the assistance of SPSS software version 25. The result indicate that menu veriety (X1) has a significant influence on purchasing decisions (Y), with a significance value of 0.006 < 0.05. Furthermore, taste (X2) also shows a significant influence, with a value of 0.022 < 0.05. Meanwhile, survice quality (X3) exhibits the strongest influence, with a value of 0.000 < 0.05. Simultaneously, all three independent variables significantly affect purchasing decisions, as evidenced by the calculated F value of 106.323 > F table 2.70 and significance of 0.000 < 0.05. The coefficient of determination (R2) of 0.769 indicates that 76.9% of the variation in purchasing decisions is influenced by these variables, while the remaining 23.1% is affected by other factros.